EFFECT OF SOIL CONSERVATION MEASTIURES ON RUNOFF AND SILT YIELD IN HIRAKUD CATCHMENT - Pradhan, K. (Journal of Soil and Water Conservation, 2022)
Land degradation and soil erosion from catchments of river valley project cause premature silting of-reservoirs. TO arrest the soil erosion problem in the catchment area different Soil Conservation measures have been taken up in different river valley projects in Drava. The programme of Soil Condensation has been implemented on the basis of priority watershed. The causes of soil erosion in the watersheds have been discussed and suggestions hare been made to counter the problem.